The sustainability of small-scale fisheries in oil-producing sections of the Gulf of Mexico. Issue 4 (December 2021) - Peña-Puch, Angelina Del Carmen; Pérez-Jiménez, Juan Carlos; Espinoza-Tenorio, Alejandro; Méndez-Loeza, Iván; Williams-Jara, Gerardo Manuel
Highlights: 25 variables potentially influencing fisheries sustainability were identified. Most of the variables of the governance and users' sub-systems need attention. Variables could be useful for assessments of small-scale fisheries sustainability. Local fishers' knowledge was useful for description of the variables. Local fishers provide 20 management suggestions to improve their fisheries. Abstract: Small-scale fisheries are complex, making them difficult to assess and manage. In this study, the authors' knowledge and findings from interviews with local users were drawn upon to identify 25 variables with the potential to influence the sustainability of small-scale fisheries in Campeche, Mexico. It is concluded that achieving sustainability in these fisheries will vary on a case-by-case basis, demanding pursuit of specific sets of variables, depending on the circumstances. Interviewees put forward a series of recommendations to strengthen Mexican regulations linked to fisheries, to empower fishers, and to facilitate effective fishery co-management.